Thermoreversible behavior of associating polymer solutions: thermothinning versus thermothickening - Hourdet, Dominique; Gadgil, Jayant; Podhajecka, K.; Badiger, Manohar V.; Brulet, A.; Wadgaonkar, P. P. (Macromolecules, 2005)
Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST similar to 32 degrees C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scattering patterns were described using a polydisperse sphere model taking into account hard-sphere interactions. This model allow us to draw a realistic picture of physical gels with quantitative information concerning the size of hydrophobic cores, the volume fraction of stickers in the aggregates, the fraction of stickers which take part in the aggregation process, the range of repulsive interactions, and the structural modifications induced by temperature. The description of the network is in good agreement with complementary data obtained from DSC and C-13 NMR. In the present work, a special emphasis has been given to the important relationship existing between the viscoelastic properties of associating polymer solutions and the binding energy of stickers leaving temporarily the micellar junction. Depending on the endothermic or exothermic nature of the disengagement process of the sticker (heat of demicellization), the relaxation time of the network and the viscoelastic properties will either decrease or increase with the temperature. The consequence is that aqueous solutions of PAAgC12 and PAAgPNIPA exhibit opposite rheological properties with the temperature, namely thermothinning and thermothickening. By mixing these two copolymers, we show that intermediate properties can be obtained but in that case a microphase-separated network is obtained as a result of copolymer segregation.

Anti-oxidant properties of ficus religiosa L. Bark extract on human keratinocytes - Dixit, Shailesh S.; Kulkarni, Atul; Seo, Hyo Hyun; Gadgil, Jayant; Dingre, Medini; Umar, Ahmad; Moh, Sang Hyun; Parasharami, Varsha A. (Science of Advanced Materials, 2016)
Ficus religiosa (Sacred Fig) is a medicinally important tree, native to the Indian subcontinent. It has been extensively pharmacologically researched species having wide spectrum of medicinal properties. All parts of F. religiosa tree are known to possess important medicinal properties such as anti-oxidant, anti-inflammatory, wound healing and skin diseases etc. However, effects of F. religiosa on skin cells line HaCaT was not studied for its antioxidant properties. In this report we have investigated F. religiosa bark aqueous extract for its antioxidant properties on human keratinocytes (HaCaT) cell line using DPPH, superoxide dismutase 1, superoxide dismutase 2 and catalase assay. We observed that F. religiosa bark aqueous extract efficiently scavenged (80%) DPPH radicals. Superoxide dismutase1 assay of F. religiosa bark aqueous extract effectively scavenged superoxide radicals (O-2(-)) and showed dose dependent activity. Reactive oxygen species were trapped by superoxide dismutase 2 assay of F. religiosa bark aqueous extract and form hydrogen peroxide. Catalase assay results revelled that hydrogen peroxide was further decomposed to give water and oxygen. Thus various anti-oxidant assays of F. religiosa bark aqueous extract indicate that it efficiently reduced the reactive oxygen species in skin cells.
Keywords: Anti-Oxidant; Catalase Assay; DPPH Assay; Ficus religiosa; Keratinocyte HaCaT Cell Line; Moraceae; SOD Assay